Comparison of nanocomposites based on nylon 6 and nylon 66 - Chavarria, F.; Paul, D.R.
Nylon 6 and nylon 6,6 organoclay nanocomposites were prepared by melt processing using a twin screw extruder. The effects of polyamide type and processing temperature on the mechanical properties and the morphology of the nanocomposites were examined. Mechanical properties, transmission electron microscopy (TEM), wide-angle X-ray diffraction (WAXD), percentage crystallinity and isothermal thermo-gravimetric analysis (TGA)data are reported. A particle analysis was performed to quantitatively characterize the morphology; these results are later employed in modeling the modulus of these materials using composite theory. No significant difference was observed in the mechanical properties and morphology of PA-6 nanocomposites processed at two different temperatures. PA-6 nanocomposites had superior mechanical properties than those made from PA-66. The tensile strength of PA-66 nanocomposites deviated from linearity at high levels of MMT. WAXD and TEM results show that the PA-6 nanocomposites are better exfoliated than the PA-66 nanocomposites, which exhibit a mixture of intercalated and exfoliated structures. Mechanical properties were consistent with the morphology. DSC reveals a higher percentage of crystallinity in the PA-66 samples. Isothermal TGA shows only a 5
Keywords: NANOCOMPOSITES; POLYAMIDES; TRANSMISSION ELECTRON MICROSCOPY